2018
DOI: 10.1016/j.biomaterials.2017.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Rational incorporation of molecular adjuvants into a hybrid nanoparticle-based nicotine vaccine for immunotherapy against nicotine addiction

Abstract: Current clinically-tested nicotine vaccines have yet shown enhanced smoking cessation efficacy due to their low immunogenicity. Achieving a sufficiently high immunogenicity is a necessity for establishing a clinically-viable nicotine vaccine. This study aims to facilitate the immunogenicity of a hybrid nanoparticle-based nicotine vaccine by rationally incorporating toll-like receptor (TLR)-based adjuvants, including monophosphoryl lipid A (MPLA), Resiquimod (R848), CpG oligodeoxynucleotide 1826 (CpG ODN 1826),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 52 publications
0
31
0
Order By: Relevance
“…Depending on the application that can span from disease diagnosis to targeted drug delivery, nanoparticles are constructed from different materials and in different forms such as polymeric, liposome based, dendrimers metals as well as hybrid. For example, liposome-polymeric hybrid nanoparticles showed promising use as immunotherapeutic agent with a potential application in noncancerous and cancerous diseases [9][10][11][12][13], while metal nanoparticles are more frequently explored as imaging and sensitizing probes enhancing radiation therapy [14]. Cancer research has been particularly interested in application of metal based nanoparticles for imaging, targeted drug delivery and radio sensitization in various cancers [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the application that can span from disease diagnosis to targeted drug delivery, nanoparticles are constructed from different materials and in different forms such as polymeric, liposome based, dendrimers metals as well as hybrid. For example, liposome-polymeric hybrid nanoparticles showed promising use as immunotherapeutic agent with a potential application in noncancerous and cancerous diseases [9][10][11][12][13], while metal nanoparticles are more frequently explored as imaging and sensitizing probes enhancing radiation therapy [14]. Cancer research has been particularly interested in application of metal based nanoparticles for imaging, targeted drug delivery and radio sensitization in various cancers [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Nicotine hapten is such a small molecule that it only elicits an immune response when attached to a carrier, such as a protein or NP. Zhao et al designed a series of nanovaccines, and their studies with mice showed that certain types of NPs exhibited the greatest ability to block nicotine from entering the brain 24 . Unfortunately, the assays conducted to date have revealed drawbacks that prevent these systems from achieving higher cessation rates than a placebo 20 .…”
Section: Vaccinesmentioning
confidence: 99%
“…To improve the therapeutic efficacy and to obtain highly localized effects with less risk of side effects as compared to systemic administration, locally delivered drug loaded biodegradable nanoparticles is an attractive option [18]. Poly (d,l-lactic-co-glycolic acid) (PLGA) nanoparticles have been widely used for a range of biomedical applications, such as drug delivery [19], vaccination [20] and immunomodulation [21]. There is minimal systemic toxicity associated with using PLGA even in the CNS as the polymer undergoes hydrolysis into lactic acid and glycolic acid, which are eliminated from the body through common metabolic pathways [22].…”
Section: Introductionmentioning
confidence: 99%